2010
DOI: 10.1161/strokeaha.110.589895
|View full text |Cite
|
Sign up to set email alerts
|

Leonurine Protects Middle Cerebral Artery Occluded Rats Through Antioxidant Effect and Regulation of Mitochondrial Function

Abstract: Background and Purpose-Oxidative stress is known to be involved in ischemic stroke. Intense interest is drawn to the therapeutic potential of Chinese herbs on ischemic stroke because many of them contain antioxidant properties. Leonurine, 1 of the active compounds from purified Herba Leonuri, was studied to evaluate its possible therapeutic effects on ischemic stroke. Method-Middle cerebral artery occlusion was selected as our model of study. The animals were pretreated with Leonurine orally for 7 days and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
70
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(72 citation statements)
references
References 26 publications
1
70
0
1
Order By: Relevance
“…The protein concentration of the supernatant was measured using the BCA method. The detections of superoxide dismutase (SOD), malonaldehyde (MDA), and glutathione peroxidase (GSH-Px) were performed via the nitroblue tetrazolium-illumination method, thiobarbituric acid method, and benzoic acid method, respectively (Loh et al, 2010;Liu et al, 2013;Zhang et al, 2014b) using commercially available kits (Nanjing Jiancheng Bioengineering Institute, Nanjing, China).…”
Section: Detection Of Sod Mda and Gsh-pxmentioning
confidence: 99%
“…The protein concentration of the supernatant was measured using the BCA method. The detections of superoxide dismutase (SOD), malonaldehyde (MDA), and glutathione peroxidase (GSH-Px) were performed via the nitroblue tetrazolium-illumination method, thiobarbituric acid method, and benzoic acid method, respectively (Loh et al, 2010;Liu et al, 2013;Zhang et al, 2014b) using commercially available kits (Nanjing Jiancheng Bioengineering Institute, Nanjing, China).…”
Section: Detection Of Sod Mda and Gsh-pxmentioning
confidence: 99%
“…6) Using middle cerebral artery occlusion model we also found Leo had neuroprotective effects. 7) The antioxidative and anti-apoptotic effects were, at least in part, involved in the underlying mechanism. But other mechanisms remain elusive.…”
mentioning
confidence: 99%
“…13) Our previous studies have shown that Leo decreased intracellular Ca 2+ 3,4) and exerted mitochondrial protective effect both in cardiomyocytes and brain. 3,7) But little was known about the mechanism underlying this phenomenon.…”
mentioning
confidence: 99%
“…A large body of evidence has indicated that leonurine is effective in preventing many disorders through many ways, including stoke [36], chronic myocardial infarction [16, 37] and acute kidney injury [38]. Yuan et al [39] found that leonurine hydrochloride (LH), an artificial chemical compound sharing the similar structure of leonurine, can protect against osteoclast-related diseases via inhibiting receptor activator NF-κB ligand (RANKL)-TNF receptor-associated factor 6 (TRAF6) and phosphatidylinositol 3-kinase (PI3K)/Akt signaling pathways.…”
Section: Discussionmentioning
confidence: 99%